Reestructuración comercial administrativa en la empresa Armonía y Color Decoraciones S.A.S. (2018)
The degree work that is developed next, is based on the administrative commercial restructuring of the company Armonía y Color Decoraciones S.A.S., which is a company dedicated to the manufacture and marketing of products for decorating and covering windows, the purpose in carrying out this project is to propose different proposals for the improvement of the organization, these proposals are raised in the commercial and administrative area in order to improve and generate greater competitiveness against the market. For the development of the first chapter, a research focused on the analysis of the environment is addressed, in order to recognize how is the behavior of the sector in the city of Bogotá, DC, as well as an internal analysis of the organization on its functional areas and your current participation in the market. For this, tools such as the PESTAL analysis were used, which allowed to recognize the main external aspects that affect the development of the company, in addition to the analysis of Porter's forces to carry out a characterization of the sector and, finally, the business diagnosis of the Chamber was made of Commerce to later be able to develop the SWOT matrix.